Microstructural evolution of cement pastes blended with two types of volcanic materials - M. Burgos, Diana; M. Cardona, Luisa; Guzmán, Álvaro; M. Anwar Hossain, Khandaker; Delvasto, Silvio (Revista de la Construcción. Journal of Construction, 2017)
This article presents results of a research about the effect to incorporate Colombian volcanic materials as a replacement of ordinary Portland cement on its hydration process. For this particular case were used Tolima volcanic material (TVM) and Puracé volcanic material (PVM). Pastes with 100% ordinary Portland cement and blended cement pastes containing 20% by of weight volcanic materials were prepared. The monitoring and identification of the hydration characteristics were carried out using Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TG/DTG) and scanning electron microscopy (SEM) at 7, 28, 90 and 360 curing days. The results indicated that the main phases of the blended cement pastes containing PVM were ettringite and calcium silicate hydrate (CSH), which confirmed the pozzolanic activity of this material. The blended cement pastes containing TVM exhibited no significant differences in hydration products compared to the reference pastes, due to its inert nature.